Abdurahman Jami’s views on Humanity (Source Study) - Lola Muzaffarovna Karimova (International Journal on Integrated Education, 2021)
In the following article the sources that Jami has over forty-five works in Persian, Turkic and Arabic are analysed. Amang the analysed data. Some of them have not reached the present day. The subjects of his works are Sufism, literature, literary and religious sciences. In addition to the individual epistles and books he wrote on Sufism, Jami sprinkled his Sufi views on all his poetic and prose works. In this respect, it is very difficult to classify his works in terms of subject.